The crystal structure of (μ4-oxo)-tri(μ4-2,2′-bipyridine-6,6′-bis(olato)-κ5 O,O′:N:N′:O″)tetrazinc(II) – methylformamide (1/1), C33H25N7O8Zn4 - Shi Zhen-Zhen; Chen Shu-Yang; Chen Jun-Ling; Yun Shu-Zhou; Fu Xing-Fang (Zeitschrift für Kristallographie - New Crystal Structures)
C33H25N7O8Zn4, triclinic, P1̄ (no. 2), a = 12.1524(7) Å, b = 12.2035(7) Å, c = 14.2730(7) Å, α = 78.669(4)°, β = 66.615(5)°, γ = 62.482(6)°, V = 1722.83(19) Å3, Z = 2, R gt(F) = 0.0405, wRref (F 2) = 0.1128, T = 293(2) K.